Model Kampanye Politik Partai Demokrasi Indonesia Perjuangan (PDI-P) pada Era Orde Baru dan Reformasi - Ahmad Rifki Nurfebriansyah; Ratnia Sholihah; Sri Zul Chairiyah (Universitas Warmadewa, 2024)
Partai Demokrasi Indonesia Perjuangan (PDI-P) is a political party in Indonesia that has gone through an era of change, from the New Order era to the Reform Era. PDI-P has experienced ups and downs in General Election results since the party was founded. PDI-P's continued success to date cannot be separated from the political campaign strategy they implemented. This research discusses the political campaign strategies carried out by the PDI-P using various methods. This research uses a qualitative approach by analyzing various articles discussing the PDI-P political campaign. The results of this research are that the PDI-P experienced a change in campaign strategy between the New Order and the Reformation. PDI-P, which initially had limited means and difficult situations during the New Order era, was able to find various campaign methods since the Reformation era which then led them to success since 2014.